Effect of Developing Psychological Immune System using Cognitive Behavioral Therapy for Reducing Psychological IllnessesAmong Youth - Nikhil Chaudhary; Dr. Tarun Kumar Sharma (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Immune system can be defined as a biological term which consists of all those bodily functions of a human body that protects us from any disease or disorder. It is basically as shield that guards against any foreign content which is not acceptable or which can create an imbalance in our body. Whereas, ‘psychological immune system’ refers to a state of one’s mind where an individual develops a resilient mental armor which is quite flexible, tough & durable enough to absorb any kind of mental health issues and its adverse effects on one’s mind and which eventually aids to preserve one’s mental wellbeing. In today’s fast growing world, people are so occupied with their work that they have totally forgotten about their health. This is gradually distorting one’s mental health and also weakening their psychological resilience. The current scenario shows that if appropriate mental health techniques or therapeutic intervention such as cognitive behavioral therapy is being used at an early stage, it can help reducing psychological illnesses quite effectively. The present research was conducted to study the effect of developing psychological immune system using CBT in order to reduce psychological illnesses among youth. A standardized inventory namely Psychological Immunity System Inventory (PISI), consists of 80 items,developed by Olah (1996, 2005, and 2012) was used which is possessing high reliability and validity. The research was conducted on 05 young adults of Delhi city suffering from depression. Techniques of CBT were applied as an intervention during five therapeutic sessions to the participants. Pre & Post testing was done. It was found that participants who were provided with CBT recorded increased levels of psychological immunity. This research study is found to be unique and useful for reducing the effects of psychological illnesses among youth.
Keywords: Psychological Immunity; Resilient; Wellbeing; Cognitive Behavioral Therapy